(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Organizations can support sustainability and guarantee regulatory compliance by implementing an Environmental Management System (EMS), a framework for strategy that helps them methodically manage their environmental implications. People may occasionally just call EMSs "EMS." EMS is a methodical cycle that aids businesses in setting environmental goals, allocating resources efficiently, and continuously improving their eco-friendly performance. A more sustainable future can be achieved through the integration of environmental concerns into an organization’s core activities. This can lead to cost savings, reduced hazards, and a stronger reputation as a responsible steward of the environment.